Human resource professionals and the adoption and effectiveness of high‐performance work practices. (1st September 2021) - Kirkpatrick, Ian; Hoque, Kim
Abstract: The human resource (HR) function has become increasingly professionalised in recent times, with the development of HR certification and degree level qualifications. In this study, we assess the implications of HR professional qualifications using data from the British 2011 Workplace Employment Relations Study. Specifically, we focus on whether the adoption of high‐performance work practices (HPWPs) is greater, and the relationship between these practices and organisational performance is stronger, in workplaces with a qualified HR professional. Our analysis reveals a mixed picture. While the presence of qualified HR professionals is associated with HPWP adoption, it is not associated with a stronger relationship between HPWPs and organisational performance. Therefore, although the results suggest that professionalisation may be having some impact on the influence of the HR function, this is far from transformational.